Identification of Nanoparticle Properties for Optimal Drug Delivery across a Physiological Cell Barrier - Aisling M. Ross; Rachel M. Cahalane; Darragh R. Walsh; Andreas M. Grabrucker; Lynnette Marcar; John J. E. Mulvihill (MDPI AG, 2023)
Nanoparticles (NPs) represent an attractive strategy to overcome difficulties associated with the delivery of therapeutics. Knowing the optimal properties of NPs to address these issues could allow for improved in vivo responses. This work investigated NPs prepared from 5 materials of 3 sizes and 3 concentrations applied to a cell barrier model. The NPs permeability across a cell barrier and their effects on cell barrier integrity and cell viability were evaluated. The properties of these NPs, as determined in water (traditional) vs. media (realistic), were compared to cell responses. It was found that for all cellular activities, NP properties determined in media was the best predictor of the cell response. Notably, ZnO NPs caused significant alterations to cell viability across all 3 cell lines tested. Importantly, we report that the zeta potential of NPs correlates significantly with NP permeability and NP-induced changes in cell viability. NPs with physiological-based zeta potential of −12 mV result in good cell barrier penetration without considerable changes in cell viability.